Mechanism of Financing Investment Activities of Insurance Companies - I. Kadirova (International Journal on Integrated Education, 2021)
The article describes the formation of the financial potential of insurance companies, authorized capital and sources of their replenishment. The dynamics of changes in the investment portfolio of insurance companies is analyzed. The impact of investment facilities on insurance companies in the country has been assessed. The article also lists several factors that affect the low investment performance of insurance companies. Opinions and forecasts of foreign experts on the development of the world insurance market are given. There are tools that affect the financial stability of insurance companies and, conversely, serious risks and the obligations of insurance companies in this regard. Suggestions and practical recommendations for improving the financial stability of insurance companies have been formed.